Influencia de la nutrición y los hábitos alimentarios en la infección por SARS-CoV-2: una revisión narrativa: Influence of nutrition and eating habits on SARS-CoV-2 infection: a narrative review - Espinoza-Cueva, Fernando Esau (2022)
The COVID-19 pandemic had a huge impact on the health of the population. The role of nutrition in the context of various infectious diseases has been widely discussed in the scientific literature. It was found that, during the pandemic, there were various changes in eating habits, highlighting the increase in vegetables, fruits, and other foods with higher nutritional value. In addition, studies suggest that nutritional status, the immune system and the presence or absence of comorbidities are factors that predispose to a greater or lesser risk of SARS-CoV-2 infection. Nutritional risk has been involved with the severity of the patient with COVID-19. In this way, the nutritional factors that influence the immune system, added to the change in eating habits during the pandemic, would determine the susceptibility to SARS-CoV-2 infection. According to the available evidence, recommendations regarding a healthy diet in susceptible people could reduce the impact of confinement.